MBA Education: Curriculum to Creation (C2C) of Potential Entrepreneurs - Baskaran, Shathees (International Journal of Innovation and Business Strategy (IJIBS), 2022)
Malaysia has greatly recognized entrepreneurs’ growth and has introduced many entrepreneurial policy inceptions to boost the number of entrepreneurs, and to create entrepreneurial interests among future generations. There is a growing development in entrepreneurship education to educate and advocate entrepreneurship start-up intentions among students. In conjunction with it, this research aimed to investigate the creation of entrepreneurial start-up intention among MBA students in Malaysia through course experience in developing entrepreneurial knowledge and entrepreneurial skills. Course experience consists of good teaching, clear goals and standards, generic skills, and motivation has accessed the development of entrepreneurial skills and knowledge, and eventually the start-up intention among students. 219 MBA students from Malaysia participated as respondents and it’s concluded that course experience has a significant relationship in developing entrepreneurial knowledge and skills and these developments do have a significant relationship in creating entrepreneurial start-up intentions. In particular, the entrepreneurial skills found to have the strongest significance in creating entrepreneurial start-up intentions. These research findings have added to the existing body of knowledge in entrepreneurial research and entrepreneurial education domain.